Solve for x 6(x-1)=9(x+2)
2 answers:
<span>Simplifying
6(x + -1) = 9(x + 2)
Reorder the terms:
6(-1 + x) = 9(x + 2)
(-1 * 6 + x * 6) = 9(x + 2)
(-6 + 6x) = 9(x + 2)
Reorder the terms:
-6 + 6x = 9(2 + x)
-6 + 6x = (2 * 9 + x * 9)
-6 + 6x = (18 + 9x)
Solving
-6 + 6x = 18 + 9x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-9x' to each side of the equation.
-6 + 6x + -9x = 18 + 9x + -9x
Combine like terms: 6x + -9x = -3x
-6 + -3x = 18 + 9x + -9x
Combine like terms: 9x + -9x = 0
-6 + -3x = 18 + 0
-6 + -3x = 18
Add '6' to each side of the equation.
-6 + 6 + -3x = 18 + 6
Combine like terms: -6 + 6 = 0
0 + -3x = 18 + 6
-3x = 18 + 6
Combine like terms: 18 + 6 = 24
-3x = 24
Divide each side by '-3'.
x = -8
Simplifying
x = -8</span>
6(x-1)=9(x+2)
6x-6=9x+18
6x=9x+24
-3x=24
-x=8
x=-8
You might be interested in
2.77 × 10 ^ ( -3 ) is the answer
Answer:
8.5
Step-by-step explanation:
Volume= base*height
V= 2 1/8*4
V= 8.5
F(g(7))= f(2×7+2)= f(16)= 4×16+21=85
Therefore: the answer is 85
Hope that helps!!
No there is 53 Friday's in a year